474 Should We Be Concerned of Oesophageal Injury in Traumatic Pneumomediastinum? – A Review of the Past 11 Years in an UGI Specialist Centre. (19th August 2022) - Shehata, Z; Shetty, V
Abstract: Aim: Pneumomediastinum is a known radiological finding after major trauma, however its significance and required investigative workup is not standardized. Furthermore, there is little evidence to suggest that traumatic pneumomediastinum is indicative of oesophageal injury. Our study set out to investigate the rate of oesophageal injury for these patients at our centre, and the relevant investigative work up that is required. Method: Medical records were retrieved our trust (Major Trauma Centre 2012 – present, UGI Centre 2009 - present) to include trauma patients with radiological pneumomediastinum admitted between 2010–2021. Demographics, mechanism of injury, length of stay, and other significant findings were collected retrospectively using the electronic patient record. Results: The data search retrieved 38 patients with traumatic pneumomediastinum. 1 patient was excluded due to incomplete records. Road traffic collisions were the most common presentation (18 patients), followed by falls (13 patients), penetrating trauma (3 patients), assault (2 patients), and workplace injury (1 patient). The median length of stay was 6 days, with 2 inpatient deaths. 1 patient had a confirmed tracheobronchial injury on initial imaging which was managed conservatively in a cardiothoracic centre, while 6 other patients underwent further oral contrast CT for suspected oesophageal injury. No patients in our dataset had a confirmed oesophageal injury. Conclusions: Oesophageal injury is rarely seen in traumatic pneumomediastinum and is usually secondary to other chest injuries causing air leak into the mediastinum. Oral contrast CT is the recommended investigation to exclude oesophageal injury.